Low-haze polyamide composition, film as well as preparation method and application of low-haze polyamide composition and film
By combining components in a specific proportion in the polyamide film and adopting a lower tensile temperature method, the problem of the decrease in strength and the increase in thermal aging effect at a high tensile temperature is solved, and a high light transmittance and low haze is prepared.
Patent Information
- Application Number
- CN202311120104.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-08-31
AI Technical Summary
The existing polyamide bidirectional tensile films have reduced strength at high tensile temperatures and increased thermal aging effect, making it difficult to avoid the production of a large number of structurally complete spherical crystals in the casting stage, resulting in film rupture.
By combining components A, component B, component C, and component D at a specific content ratio, a low haze polyamide composition with low crystal regularity and weak intermolecular action force was prepared, and bidirectional stretching was performed using a lower stretching temperature to form a polyamide film with high light transmittance and low haze.
A polyamide bidirectional stretch film with high light transmittance and low haze at a lower tensile temperature is achieved, and the problems of reducing strength and increasing thermal aging effects at a high tensile temperature are avoided.
Smart Images

Figure CN119552497A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polyamide films, and more particularly to a low-haze polyamide composition, a film, and a preparation method and application thereof. Background Art
[0002] Polyamide biaxially oriented film has excellent mechanical properties, gas barrier properties, food preservation properties, heat and oil resistance, etc., and is widely used in the field of packaging films. Due to the biaxially oriented orientation of polyamide, the molecular chain orientation effect is enhanced, the crystallinity is increased, and the mechanical properties, transparency and gas barrier properties are significantly enhanced. It is a very promising barrier packaging material.
[0003] The amide group of polyamide molecules is an important reason for the high crystallinity of polyamide. The strong hydrogen bonding between polyamide molecules makes it very easy to quickly crystallize into spherulites with complete structures. For example, the spherulite growth rate of nylon 6 with a number average molecular weight of about 28,000 at 140°C can reach about 3,000 nm / s. The presence of spherulites will act as stress concentration points and cause film breakage during biaxial stretching. The strong hydrogen bonds in the spherulites make the cast film strong and tough, and the stretching temperature is high, making it difficult to stretch. Although biaxial stretching of polyamide can be achieved at high stretching temperatures, at high stretching temperatures, the polyamide molecules have a relaxation process of orientation and deorientation, which will reduce the strength of the film. In addition, at high stretching temperatures, the thermal aging effect of the film increases. Therefore, appropriately reducing the crystallization ability of polyamide and avoiding the generation of a large number of spherulites with complete structures in the casting stage are the key to biaxially stretched polyamide films. Summary of the invention
[0004] In order to solve the above problems existing in the prior art, the present invention provides a low-haze polyamide composition, and specifically relates to a low-haze polyamide composition, a film, and a preparation method and application thereof.
[0005] The object of the present invention is to provide a novel polyamide composition with high light transmittance and low haze, as well as a biaxially stretched film of the polyamide composition and a preparation method thereof.
[0006] The inventors unexpectedly discovered that when component A, component B, component C, and component D of the present invention are compounded at a specific content ratio, the resulting crystal regularity is low, the intermolecular force is weak, and a polyamide biaxially stretched film with high light transmittance and low haze can be obtained at a relatively low stretching temperature; thus, the present invention is completed.
[0007] One of the objects of the present invention is to provide a low haze polyamide composition, which comprises a blended polyamide and mixed olefin-maleic anhydride copolymer microspheres;
[0008] The composition may specifically include component A and / or component B, and further include component C and component D. The blended polyamide may include at least one of component A and component B, and further include component C. Component A is PA6, component B is PA612, component C is MXD6, and component D is olefin-maleic anhydride copolymer microspheres.
[0009] Among them, the weight ratio of component A to component B can be (0-100):(100-0), preferably (60-95):(5-40); more preferably (70-90):(10-30); for example, the specific weight ratio can be 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, 95:5 or any value between the above values or a numerical range between any two of the above values.
[0010] The weight ratio of component C to component (A+B) may be (5-50):(50-95), preferably (10-40):(60-90). For example, the specific weight ratio may be 5:95, 10:90, 15:85, 20:80, 30:70, 40:60, 50:50, or any value between the above values or a numerical range between any two of the above values.
[0011] Taking the total weight of component A, component B and component C as 100 parts by weight,
[0012] The weight ratio of component D to component (A+B+C) may be (0.01-0.35):100, preferably (0.03-0.2):100, and more preferably (0.03-0.1):100. For example, the specific weight ratio may be 0.01:100, 0.02:100, 0.03:100, 0.04:100, 0.05:100, 0.06:100, 0.07:100, 0.08:100, 0.09:100, 0.10:100, 0.15:100, 0.18:100, 0.20:100, 0.25:100, 0.30:100, or any value between the above values or a numerical range between any two of the above values.
[0013] According to the present invention, the relative viscosity of PA6 is 1.5-5.0, preferably 2.0-4.0, and the viscosity test standard is ISO307; and / or,
[0014] According to the present invention, the relative viscosity of PA612 is 1.5-5.0, preferably 2.0-4.0, and the viscosity test standard is ISO307; and / or,
[0015] According to the present invention, the relative viscosity of the MXD6 is 1.5-5.0, preferably 2.0-4.0, and the viscosity test standard is ISO307.
[0016] The low haze polyamide composition according to the present invention may also include at least one of nylon 66, nylon 610, nylon 11, nylon 12, nylon 1012, nylon 46, nylon 69, nylon 6T, nylon 6 / 66, nylon 66 / 6T, nylon 6T / 6I, etc. In the specific implementation process, a proper amount of the low haze polyamide composition may be added in the form of a mixture, a copolymer or a complex, for example, a composition of components A, C, and D; a composition of components B, C, and D; a composition of components A, B, C, and D, etc.
[0017] According to the present invention, the component D is mixed olefin-maleic anhydride copolymer microspheres, preferably with a particle size of 100-300 nm.
[0018] In the present invention, the composition contains mixed olefin-maleic anhydride copolymer microspheres of the above particle size. The particle size can be measured by scanning electron microscopy.
[0019] In the present invention, preferably, the mixed olefin-maleic anhydride copolymer microspheres are copolymer microspheres of maleic anhydride and C4 olefins prepared by copolymerization of mixed C4 and maleic anhydride in the presence of nitrogen, an initiator and an organic solvent. The alternating copolymerization reaction can be a one-step reaction using a precipitation polymerization method.
[0020] Preferably, the copolymerization reaction temperature may be 80-100° C., and the copolymerization reaction pressure may be 0.8-2 MPa.
[0021] In a specific implementation, the content of maleic anhydride structural units in the mixed olefin-maleic anhydride copolymer microspheres can be 40 to 70 mol%, preferably 45 to 60 mol%, and more preferably 48 to 55 mol%. In the mixed olefin-maleic anhydride copolymer microspheres, the maleic anhydride structural units can be in the main chain, the side chain, or the end group. The content of maleic anhydride structural units can be determined by 1 H and 13 The mixed olefin-maleic anhydride copolymer microspheres may also contain olefin structural units formed from at least one of 1-butene, 1,3-butadiene and isobutylene. The content of the olefin structural units in the mixed olefin-maleic anhydride copolymer microspheres can be determined by 1 H and 13 For example, the content of the olefin structural unit in the mixed olefin-maleic anhydride copolymer microspheres can be 45 to 55 mol%.
[0022] In a specific implementation, the mixed olefin-maleic anhydride copolymer microspheres can be copolymer microspheres of maleic anhydride, n-butene and isobutylene. The mixed olefin-maleic anhydride copolymer microspheres mainly contain structural units from n-butene and isobutylene, and the content can be 45-55 mol%.
[0023] The mixed olefin-maleic anhydride copolymer microspheres used in the present invention can be made of mixed C4 as a raw material, and the mixed C4 can come from a variety of petroleum refining processes, and can be C 4 A mixture of hydrocarbon compounds. Preferably, the mixed C4 may contain at least one of 1-butene, isobutylene, 1,3-butadiene, n-butane, isobutane, cis-2-butene and trans-2-butene, for example, it may be liquefied fuel produced in the process of petroleum refining, cracked gas produced by cracking of naphtha, gas produced by methanol to olefins, etc. The composition of the mixed C4 can be analyzed by gas chromatography using Agilent's 7890A gas chromatograph (GC).
[0024] Specifically, the composition content of the mixed carbon tetraene can be 1 to 99 weight % of 1-butene, 1 to 99 weight % of isobutylene, 0 to 99 weight % of 1,3-butadiene, 0 to 50 weight % of 1,2-butadiene, 0 to 99 weight % of n-butane, 1 to 99 weight % of isobutane, 5 to 20 weight % of vinyl acetylene, 0 to 99 weight % of cis-2-butene and 1 to 99 weight % of trans-2-butene.
[0025] According to a preferred embodiment of the present invention, the composition content of the mixed carbon tetraoxide can be 5-10% by weight of 1-butene, 5-15% by weight of isobutylene, 10-20% by weight of 1,3-butadiene, 5-15% by weight of 1,2-butadiene, 0.5-5% by weight of n-butane, 0.5-2% by weight of isobutane, 20-40% by weight of cis-2-butene, 2-10% by weight of trans-2-butene, and 5-20% by weight of vinyl acetylene.
[0026] According to another preferred embodiment of the present invention, the composition content of the mixed carbon tetraene can be 0.1-2 weight % of 1-butene, 10-30 weight % of isobutylene, 0.01-0.1 weight % of 1,3-butadiene, 0.5-5 weight % of n-butane, 30-40 weight % of isobutane, 20-40 weight % of cis-2-butene, and 5-20 weight % of trans-2-butene.
[0027] According to another preferred embodiment of the present invention, the composition content of the mixed carbon tetracarbonate can be 5-15% by weight of 1-butene, 0.5-3% by weight of isobutylene, 20-30% by weight of n-butane, 15-30% by weight of cis-2-butene, and 35-45% by weight of trans-2-butene.
[0028] In the present invention, 1-butene, isobutylene and 1,3-butadiene in the mixed C4 can be copolymerized with maleic anhydride. Preferably, the weight ratio of the mixed C4 to maleic anhydride is (0.2-3):1; preferably (0.8-3):1.
[0029] In the present invention, the amount of the initiator is sufficient to ensure that the copolymerization reaction proceeds. Preferably, the amount of the initiator can be 0.05 to 20 mol% of maleic anhydride, and the specific amount can be adjusted according to actual conditions. The initiator can be dibenzoyl peroxide or azobisisobutyronitrile.
[0030] In the present invention, the organic solvent is an inert solvent that does not participate in the copolymerization reaction and provides a dispersion medium for the copolymerization reaction. Preferably, the concentration of maleic anhydride in the organic solvent is 5 wt % to 25 wt %; preferably 10 wt % to 20 wt %. The organic solvent is preferably at least one of isoamyl acetate, butyl acetate, isopropyl acetate and ethyl acetate.
[0031] In the present invention, the copolymerization conditions can achieve the copolymerization of the C4 olefin in the mixed C4 with maleic anhydride. Preferably, the copolymerization temperature can be 60 to 100° C., preferably 80 to 100° C., the copolymerization pressure can be 0.5 to 2 MPa, preferably 0.8 to 2 MPa, and the copolymerization time can be 5 to 10 hours.
[0032] In the present invention, a certain amount of mixed C4 can be introduced into a reactor containing a certain amount of maleic anhydride, initiator and organic solvent, copolymerization reaction is carried out under nitrogen atmosphere and the above copolymerization reaction conditions, and then the reaction product is flash separated and centrifuged to obtain the mixed olefin-maleic anhydride copolymer microspheres. Wherein, the amount of mixed C4, maleic anhydride, initiator and organic solvent is as described above. Flash separation can be carried out in a flash separator at about 25°C and 0MPa. The centrifugal separation can be carried out at a speed of about 4000rpm for about 20min. The obtained microspheres can also be further washed with hexane and filtered with a sand core to obtain a filter cake, and the filter cake is vacuum dried at about 90°C for about 8h, and the obtained product can be analyzed for its composition content and used for the polyamide composition.
[0033] In the present invention, the polyamide composition may further contain an additive, which may be an additive that has a positive effect on other properties of the polyamide film and does not adversely affect the stretch film-forming property, mechanical properties and optical properties of the polyamide film. The additive may be, for example, at least one of an antioxidant, a slip agent, a lubricant, a plasticizer, an acid absorbent, an antistatic agent and an anti-adhesive agent.
[0034] The second object of the present invention is to provide a method for preparing the low haze polyamide composition, which may include the following steps:
[0035] The components including the component A and / or the component B, the component C and the component D are blended to obtain the low haze polyamide composition.
[0036] The third object of the present invention is to provide a polyamide molded product made from the low haze polyamide composition, wherein the content of the low haze polyamide composition can be 80-100% by weight.
[0037] The fourth object of the present invention is to provide a film made from the low haze polyamide composition, preferably a biaxially stretched film. Preferably, the biaxially stretched film has a thickness ranging from 5 to 120 microns, preferably from 10 to 100 microns.
[0038] A fifth object of the present invention is to provide a method for preparing the film. The method may include the following steps:
[0039] The low haze polyamide composition is melt-extruded and cast into a sheet to obtain a polyamide sheet; the polyamide sheet is stretched to form a film; and the stretching is preferably biaxial stretching.
[0040] The specific steps may include:
[0041] (1) preparing a mixture of components including component A and / or component B, component C, and component D;
[0042] (2) melt-extruding the mixture and casting a sheet to obtain a polyamide sheet;
[0043] (3) Biaxially stretching the polyamide cast sheet to form a film. The stretching temperature may be 90-185°C, preferably 95-175°C, and more preferably 100-165°C.
[0044] According to the present invention, step (1) mainly provides a mixture of the components contained in the above composition so as to form a polyamide film through subsequent processing. Preferably, step (1) comprises: mixing PA6, PA612, MXD6 and a mixed olefin-maleic anhydride copolymer in a high-speed mixer.
[0045] According to the present invention, before performing step (2), the mixture obtained in step (1) can also be subjected to extrusion granulation (the temperature of extrusion granulation can be 120-275° C.), and the obtained mixture can be used for the operation of step (2).
[0046] According to the present invention, the step (2) of melt-extruding the mixture and casting the cast sheet can be carried out in a casting machine. Preferably, the temperature of the melt extrusion can be 235-280°C, preferably 240-270°C; the temperature of the casting quenching roller of the cast sheet is 15-70°C, preferably 20-60°C.
[0047] According to the present invention, the casting die used for the cast sheet can be selected according to the structure of the film to be obtained. For example, when a film with a single-layer structure is required, a single-layer die can be used; when a film with a multi-layer structure (a film with a three-layer structure of an upper surface layer, a core layer and a lower surface layer) is required, a multi-layer composite die can be used, and at least one layer (core layer) of the multi-layer composite die is connected to the extruder hopper filled with the above-mentioned polyamide composition, so that at least one layer (core layer) in the obtained casting sheet can be a polyamide layer formed by the above-mentioned polyamide composition. Of course, the multi-layer composite die can also be connected to the extruder hopper filled with the above-mentioned polyamide composition, so that each layer in the obtained casting sheet can be a polyamide layer formed by the above-mentioned polyamide composition.
[0048] To this end, the polyamide casting sheet is a single-layer structure or a multi-layer structure, preferably a three-layer structure consisting of an upper surface layer, a core layer and a lower surface layer, wherein the upper surface layer, the core layer and the lower surface layer are all layers formed of a polyamide composition.
[0049] According to the present invention, in step (3), the biaxial stretching may include synchronous stretching or stepwise stretching. The synchronous stretching refers to stretching the film in the longitudinal direction (MD) and transverse direction (TD) at the same time, and the stepwise stretching refers to first stretching the film in the longitudinal direction and then stretching the film in the transverse direction.
[0050] Preferably, the synchronous stretching comprises preheating the polyamide casting sheet first, and then simultaneously stretching the polyamide casting sheet in MD and TD. Preferably, the synchronous stretching comprises: the stretching temperature may be 90-185°C, preferably 95-175°C, and more preferably 100-165°C.
[0051] The MD stretching ratio is 2.5 times or more (for example, 2.5-6 times), the TD stretching ratio is 2.5 times or more (for example, 2.5-6 times), the MD stretching rate is 100% / s or more (for example, 100% / s-500% / s), and the TD stretching rate is 100% / s or more (for example, 100% / s-500% / s).
[0052] Preferably, the step-by-step stretching comprises: preheating the polyamide casting sheet first, then stretching it in MD, and then preheating it again and then stretching it in TD. Preferably, the step-by-step stretching conditions include: the MD stretching temperature can be 90-185°C, preferably 95-175°C, and more preferably 100-165°C; the TD stretching temperature can be 90-185°C, preferably 95-175°C, and more preferably 100-165°C.
[0053] The MD stretching ratio is 2.5 times or more (for example, 2.5-6 times), the TD stretching ratio is 2.5 times or more (for example, 2.5-6 times), the MD stretching rate is 100% / s or more (for example, 100% / s-200% / s), and the TD stretching rate is 100% / s or more (for example, 100% / s-200% / s).
[0054] According to the present invention, the method may or may not perform an annealing and shaping treatment on the stretched film. In the case of performing the shaping treatment, that is, the method further comprises performing an annealing and shaping treatment on the obtained film after step (3), and the temperature of the annealing and shaping treatment is preferably 180-200° C. The time of the annealing and shaping treatment is preferably 5-60 seconds. Performing the annealing and shaping treatment on the stretched film can improve the dimensional stability of the film.
[0055] According to the present invention, the method may further include subjecting the obtained polyamide film to surface corona treatment, edge cutting and winding treatment, which are conventional operations in the art and are not particularly limited by the present invention.
[0056] The sixth object of the present invention is to provide the application of the low-haze polyamide composition or the film.
[0057] The invention can obtain a biaxially stretched polyamide film with high light transmittance, low haze and low stretching temperature, and can be used in the field of packaging films. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is an isothermal polarized image photograph (POM) of the cast sheet of Example 3, magnified 500 times;
[0059] Figure 2 This is an isothermal polarized image photograph (POM) of the cast sheet of Comparative Example 1, magnified 500 times. DETAILED DESCRIPTION
[0060] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0061] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0062] Source of raw materials
[0063] PA6-1 was purchased from Xinhui Meida, with a relative viscosity of 3.4;
[0064] PA6-2 was purchased from Xinhui Meida, with a relative viscosity of 4.0;
[0065] PA612-1 was purchased from Yingku Chemical, with a relative viscosity of 3.1;
[0066] PA612-2 was purchased from Yingku Chemical, with a relative viscosity of 2.6;
[0067] MXD6 Yinggu chemical M30m, relative viscosity 2.6;
[0068] The composition of mixed C4A (weight percentage) is: 1,2-butadiene, 7.45%; 1,3-butadiene, 20.04%; 1-butene, 9.19%; trans-2-butene, 6.27%; cis-2-butene, 34.6%; vinyl acetylene, 5.03%; isobutane, 0.68%; isobutylene, 13.72%; n-butane 1.5%, others, 1.52%;
[0069] The composition of mixed C4B (weight percentage) is: 1,2-butadiene 0.03%; 1,3-butadiene, 0.02%; trans-2-butene, 19.26%; isobutane, 30.49%; isobutylene, 10.2%; cis-2-butene, 32.41%; 1-butene, 1.47%; n-butane, 4.87%; others, 1.25%;
[0070] The composition of the mixed C4 (weight percentage) is: trans-2-butene, 43.11%; cis-2-butene, 17.92%; n-butane 26.63%; 1-butene, 5.64%; isobutylene, 3.2%; others, 3.5%;
[0071] The tensile strength and elongation at break of biaxially oriented polyamide films were measured according to the method specified in GB / T 1040.3-2006;
[0072] The haze and light transmittance of biaxially oriented polyamide films were measured according to the method specified in GB / T 2410-2008;
[0073] The oxygen permeability of the biaxially oriented polyamide film was measured according to the method specified in ASTM D-3985;
[0074] The isothermal polarized image was measured by a Japanese OLYMPUS BX51 polarizing microscope under the following conditions: The temperature was raised from room temperature to 270°C at a rate of 40°C / min, and then kept constant for 3 minutes, then cooled to 220°C at a rate of 10°C / min, and the crystallization process was observed at a constant temperature.
[0075] The content of maleic anhydride structural units in mixed olefin-maleic anhydride copolymer microspheres was determined by 1 H and 13 C NMR determination;
[0076] The particle size of the mixed olefin-maleic anhydride copolymer microspheres was measured by scanning electron microscopy.
[0077] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0078] Example 1
[0079] This example is used to illustrate the polyamide composition and polyamide film and the preparation method thereof of the present invention.
[0080] (1) Preparation of mixed olefin-maleic anhydride copolymer microspheres
[0081] Under nitrogen protection, 6.3 kg of mixed carbon tetrachloride was introduced into a 200 L reactor containing 21 kg of maleic anhydride, 6 kg of azobisisobutyronitrile and 100 L of isoamyl acetate as an organic reaction liquid for copolymerization. The copolymerization pressure was 1.3 MPa, the copolymerization temperature was 80 ° C, and the copolymerization time was 5 h.
[0082] The copolymerization product was passed into a flash separator for gas-liquid separation at 25°C and 0MPa. The obtained liquid-solid mixture was centrifuged in a centrifugal separator at 4000rpm for 20min for liquid-solid separation to obtain a solid product, which was then washed with hexane. The filter cake obtained by filtration through a sand core funnel was vacuum dried at 90°C for 8h to obtain a copolymer powder, which was the mixed olefin-maleic anhydride copolymer microsphere. The copolymer powder was tested, and the content of the maleic anhydride structural unit was 52.3 mol%; the average particle diameter was 100nm;
[0083] (2) 81 parts by weight of PA6-1, 9 parts by weight of PA612-1 and 10 parts by weight of MXD6 were weighed and mixed in a high-speed mixer to obtain a blended polyamide; 0.03 parts by weight of mixed olefin-maleic anhydride copolymer microspheres were weighed and mixed with the blended polyamide, and then added to the core layer extruder and the upper and lower surface layer extruders of a multi-layer extrusion casting machine model LCR400 of Swedish Labtech Company for melt extrusion and casting, the temperature of each melt extrusion section was 240-270° C., and the temperature of the casting chill roll was 25° C., thereby obtaining a polyamide casting sheet consisting of an upper surface layer, a core layer and a lower surface layer;
[0084] (3) placing the polyamide casting sheet into a stretching fixture of a film biaxial stretching device, preheating the polyamide casting sheet, and then simultaneously performing MD stretching and TD stretching; the conditions include: preheating temperature of 105° C., stretching temperature of 105° C., MD stretching ratio of 3 times, MD stretching rate of 100% / s, TD stretching ratio of 3 times, and TD stretching rate of 100% / s;
[0085] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0086] Example 2
[0087] This example is used to illustrate the polyamide composition and polyamide film and the preparation method thereof of the present invention.
[0088] (1) Preparation of mixed olefin-maleic anhydride copolymer microspheres
[0089] Under nitrogen protection, 20 kg of mixed carbon tetra B was introduced into a 200 L reactor containing 20 kg of maleic anhydride, 3.5 kg of dibenzoyl peroxide and 100 L of isoamyl acetate as an organic reaction liquid for copolymerization. The copolymerization pressure was 1.2 MPa, the copolymerization temperature was 90 ° C, and the copolymerization time was 8 h.
[0090] The copolymerization product was passed into a flash separator for gas-liquid separation at 25°C and 0MPa, and the obtained liquid-solid mixture was further centrifuged in a centrifugal separator at 4000rpm for 20min for liquid-solid separation to obtain a solid product, which was then washed with hexane, and the filter cake obtained by suction filtration through a sand core funnel was vacuum dried at 90°C for 8h to obtain a copolymer powder. The copolymer powder was tested, and the content of maleic anhydride structural units was 52.6 mol%; the average particle diameter was 300nm;
[0091] (2) Weighing 42 parts by weight of PA6-1, 18 parts by weight of PA612-1 and 40 parts by weight of MXD6, and mixing them uniformly in a high-speed mixer to obtain a blended polyamide; Weighing 0.1 parts by weight of mixed olefin-maleic anhydride copolymer microspheres, mixing them uniformly with the blended polyamide, and adding them to the core layer extruder and the upper and lower surface layer extruders of a multi-layer extrusion casting machine model LCR400 of Swedish Labtech Company for melt extrusion and casting, wherein the temperature of each melt extrusion section is 240-270° C., and the temperature of the casting chill roll is 35° C., thereby obtaining a polyamide casting sheet consisting of an upper surface layer, a core layer and a lower surface layer;
[0092] (3) The polyamide casting sheet is placed in the stretching fixture of the film biaxial stretching equipment, the polyamide casting sheet is preheated first, and then MD stretching and TD stretching are performed simultaneously; the conditions include: preheating temperature is 105°C, stretching temperature is 105°C, MD stretching ratio is 3.5 times, MD stretching rate is 200% / s, TD stretching ratio is 3.5 times, TD stretching rate is 200% / s; finally, a film with an average thickness of 20 μm is obtained, which is composed of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer are the polyamide composition of this embodiment. The properties of the obtained biaxially stretched film are shown in Table 1.
[0093] Example 3
[0094] This example is used to illustrate the polyamide composition and polyamide film and the preparation method thereof of the present invention.
[0095] (1) Preparation of mixed olefin-maleic anhydride copolymer microspheres
[0096] Under nitrogen protection, 10 kg of mixed carbon tetracarbon was introduced into a 200 L reactor containing 20 kg of maleic anhydride, 5.0 kg of dibenzoyl peroxide and 100 L of isoamyl acetate as an organic reaction liquid for copolymerization. The copolymerization pressure was 1.35 MPa, the copolymerization temperature was 85 ° C, and the copolymerization time was 6 h.
[0097] The copolymerization product was passed into a flash separator for gas-liquid separation at 25°C and 0MPa, and the obtained liquid-solid mixture was further centrifuged in a centrifugal separator at 6000rpm for 20min for liquid-solid separation to obtain a solid product, which was then washed with hexane, and the filter cake obtained by suction filtration through a sand core funnel was vacuum dried at 90°C for 8h to obtain a copolymer powder. The copolymer powder was tested, and the content of maleic anhydride structural units was 50.2 mol%; the average particle diameter was 200nm.
[0098] (2) 72.25 parts by weight of PA6-1, 12.75 parts by weight of PA612-1 and 15 parts by weight of MXD6 were weighed and mixed in a high-speed mixer to obtain a blended polyamide; 0.06 parts by weight of mixed olefin-maleic anhydride copolymer microspheres were weighed and mixed with the blended polyamide, and then added to the core layer extruder and the upper and lower surface layer extruders of a multi-layer extrusion casting machine model LCR400 of Swedish Labtech Company for melt extrusion and casting, the temperature of each melt extrusion section was 240-270° C., and the temperature of the casting chill roll was 30° C., thereby obtaining a polyamide casting sheet consisting of an upper surface layer, a core layer and a lower surface layer;
[0099] (3) placing the polyamide casting sheet into a stretching fixture of a film biaxial stretching device, preheating the polyamide casting sheet, and then simultaneously performing MD stretching and TD stretching; the conditions include: preheating temperature of 100° C., stretching temperature of 100° C., MD stretching ratio of 3 times, MD stretching rate of 100% / s, TD stretching ratio of 3 times, and TD stretching rate of 100% / s;
[0100] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0101] Example 4
[0102] This example is used to illustrate the polyamide composition and polyamide film and the preparation method thereof of the present invention.
[0103] (1) Preparation of mixed olefin-maleic anhydride copolymer microspheres. Copolymer microspheres were prepared according to the method of step (1) in Example 1, and the particle diameter was 100 nm.
[0104] (2) 80.75 parts by weight of PA6-1, 4.25 parts by weight of PA612-1 and 15 parts by weight of MXD6 were weighed and mixed in a high-speed mixer to obtain a blended polyamide; 0.03 parts by weight of mixed olefin-maleic anhydride copolymer microspheres were weighed and mixed with the blended polyamide, and then added to the core layer extruder and the upper and lower surface layer extruders of a multi-layer extrusion casting machine model LCR400 of Swedish Labtech Company for melt extrusion and casting, the temperature of each melt extrusion section was 240-270° C., and the temperature of the casting chill roll was 40° C., thereby obtaining a polyamide casting sheet consisting of an upper surface layer, a core layer and a lower surface layer;
[0105] (3) placing the polyamide casting sheet into the stretching fixture of the film biaxial stretching equipment, preheating the polyamide casting sheet, and then simultaneously performing MD stretching and TD stretching; the conditions include: preheating temperature of 105° C., stretching temperature of 105° C., MD stretching ratio of 3.5 times, MD stretching rate of 200% / s, TD stretching ratio of 3.5 times, and TD stretching rate of 200% / s;
[0106] Finally, a film with an average thickness of 20 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0107] Example 5
[0108] This example is used to illustrate the polyamide composition and polyamide film and the preparation method thereof of the present invention.
[0109] (1) Preparation of mixed olefin-maleic anhydride copolymer microspheres. Copolymer microspheres were prepared according to the method of step (1) in Example 1, and the average particle diameter was 100 nm.
[0110] (2) Weighing 51 parts by weight of PA6-1, 34 parts by weight of PA612-1 and 15 parts by weight of MXD6, and mixing them uniformly in a high-speed mixer to obtain a blended polyamide; Weighing 0.03 parts by weight of mixed olefin-maleic anhydride copolymer microspheres, mixing them uniformly with the blended polyamide, and adding them to the core layer extruder and the upper and lower surface layer extruders of a multi-layer extrusion casting machine model LCR400 of Swedish Labtech Company for melt extrusion and casting, the temperature of each melt extrusion section is 240-270° C., and the temperature of the casting chill roll is 25° C., thereby obtaining a polyamide casting sheet consisting of an upper surface layer, a core layer and a lower surface layer;
[0111] (3) placing the polyamide casting sheet into a stretching fixture of a film biaxial stretching device, preheating the polyamide casting sheet, and then simultaneously performing MD stretching and TD stretching; the conditions include: preheating temperature of 105° C., stretching temperature of 105° C., MD stretching ratio of 3 times, MD stretching rate of 300% / s, TD stretching ratio of 3 times, and TD stretching rate of 300% / s;
[0112] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0113] Example 6
[0114] (1) Preparation of mixed olefin-maleic anhydride copolymer microspheres. Copolymer microspheres were prepared according to the method of step (1) in Example 1, and the particle diameter was 100 nm.
[0115] (2) Weighing 95 parts by weight of PA6-1 and 5 parts by weight of MXD6 and mixing them uniformly in a high-speed mixer to obtain a blended polyamide; Weighing 0.01 parts by weight of mixed olefin-maleic anhydride copolymer microspheres, mixing them uniformly with the blended polyamide, and adding them to the core layer extruder and the upper and lower surface layer extruders of a multi-layer extrusion casting machine model LCR400 of Swedish Labtech Company for melt extrusion and casting, the temperature of each melt extrusion section is 240-270° C., and the temperature of the casting chill roll is 30° C., thereby obtaining a polyamide casting sheet consisting of an upper surface layer, a core layer and a lower surface layer;
[0116] (3) placing the polyamide casting sheet into a stretching fixture of a film biaxial stretching device, preheating the polyamide casting sheet, and then simultaneously performing MD stretching and TD stretching; the conditions include: preheating temperature of 105° C., stretching temperature of 105° C., MD stretching ratio of 4 times, MD stretching rate of 300% / s, TD stretching ratio of 4 times, and TD stretching rate of 300% / s;
[0117] Finally, a film with an average thickness of 15 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0118] Example 7
[0119] (1) Preparation of mixed olefin-maleic anhydride copolymer microspheres. Copolymer microspheres were prepared according to the method of step (1) in Example 1, and the particle diameter was 100 nm.
[0120] (2) 95 parts by weight of PA612-1 and 5 parts by weight of MXD6 were mixed in a high-speed mixer to obtain a blended polyamide; 0.35 parts by weight of mixed olefin-maleic anhydride copolymer microspheres of the blended polyamide were weighed, mixed with the blended polyamide, and then added to the core layer extruder and the upper and lower surface layer extruders of a multi-layer extrusion casting machine model LCR400 of Swedish Labtech Company for melt extrusion and casting, the temperature of each melt extrusion section was 240-270° C., and the temperature of the casting chill roll was 25° C., thereby obtaining a polyamide casting sheet consisting of an upper surface layer, a core layer and a lower surface layer;
[0121] (3) placing the polyamide casting sheet into a stretching fixture of a film biaxial stretching device, preheating the polyamide casting sheet, and then simultaneously performing MD stretching and TD stretching; the conditions include: preheating temperature of 105° C., stretching temperature of 105° C., MD stretching ratio of 3 times, MD stretching rate of 200% / s, TD stretching ratio of 3 times, and TD stretching rate of 200% / s;
[0122] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0123] Example 8
[0124] (1) Preparation of mixed olefin-maleic anhydride copolymer microspheres. Copolymer microspheres were prepared according to the method of step (1) in Example 1, and the particle diameter was 100 nm.
[0125] (2) 25 parts by weight of PA6-1, 25 parts by weight of PA612-1 and 50 parts by weight of MXD6 are uniformly mixed in a high-speed mixer to obtain a blended polyamide; 0.01 parts by weight of mixed olefin-maleic anhydride copolymer microspheres of the blended polyamide are weighed, the mixture is uniformly mixed with the blended polyamide, and then added to a core layer extruder and an upper and lower surface layer extruder of a multi-layer extrusion casting machine model LCR400 produced by Swedish Labtech Company for melt extrusion and casting, wherein the temperature of each melt extrusion section is 240-270° C., and the temperature of the casting chill roll is 25° C., thereby obtaining a polyamide casting sheet consisting of an upper surface layer, a core layer and a lower surface layer;
[0126] (3) placing the polyamide casting sheet into a stretching fixture of a film biaxial stretching device, preheating the polyamide casting sheet, and then simultaneously performing MD stretching and TD stretching; the conditions include: preheating temperature of 105° C., stretching temperature of 105° C., MD stretching ratio of 3 times, MD stretching rate of 200% / s, TD stretching ratio of 3 times, and TD stretching rate of 200% / s;
[0127] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0128] Example 9
[0129] This example is used to illustrate the polyamide composition and polyamide film and the preparation method thereof of the present invention.
[0130] The method described in Example 8 is different in that the specific types of component A and component B used are PA6-2 and PA612-2 respectively;
[0131] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0132] Example 10
[0133] This example is used to illustrate the polyamide composition and polyamide film and the preparation method thereof of the present invention.
[0134] The method according to Example 3, except that:
[0135] Step (3) adopts a step-by-step biaxial stretching method, and the specific operation is: preheating the polyamide casting sheet, and then first performing MD stretching, and then preheating and then performing TD stretching; the conditions include: the preheating temperature before MD stretching is 105°C, the MD stretching temperature is 105°C, the MD stretching ratio is 3 times, and the film MD stretching rate is 100% / s; the preheating temperature before TD stretching is 105°C, the TD stretching temperature is 105°C, the TD stretching ratio is 3 times, and the film TD stretching rate is 200% / s;
[0136] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0137] Embodiment 11
[0138] This example is used to illustrate the polyamide composition and polyamide film and the preparation method thereof of the present invention.
[0139] The method described in Example 3 is different in that step (3) adopts a step-by-step biaxial stretching method, and the specific operation is: preheating the polyamide casting sheet, and then first performing MD stretching, and then preheating and then performing TD stretching; the conditions include: the preheating temperature before MD stretching is 100°C, the MD stretching temperature is 100°C, the MD stretching ratio is 3 times, and the film MD stretching rate is 300% / s; the preheating temperature before TD stretching is 100°C, the TD stretching temperature is 100°C, the TD stretching ratio is 4 times, and the film TD stretching rate is 300% / s;
[0140] Finally, a film with an average thickness of 15 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0141] Comparative Example 1
[0142] The method according to Example 1, except that component B, component C and component D are not added;
[0143] The resulting cast film was broken during the biaxial stretching process.
[0144] Comparative Example 2
[0145] The method according to Example 10, except that component B, component C and component D are not added;
[0146] The resulting cast film was broken during the biaxial stretching process.
[0147] Comparative Example 3
[0148] According to the method described in Example 1, except that component C is not added, the blended polyamide comprises 90 parts by weight of PA6-1 and 10 parts by weight of PA612-1;
[0149] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0150] Comparative Example 4
[0151] According to the method described in Example 1, except that component D is not added;
[0152] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0153] Comparative Example 5
[0154] According to the method described in Example 1, except that components A and B are not added, the blended polyamide comprises 100 parts by weight of MXD6;
[0155] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0156] Comparative Example 6
[0157] According to the method described in Example 1, except that the added amount of component D is 0.4 parts by weight, the obtained cast film breaks during the biaxial stretching process.
[0158] Comparative Example 7
[0159] The method described in Example 1 is followed, except that the amount of component D added is 0.005 parts by weight.
[0160] Finally, a film with an average thickness of 25 μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this embodiment. The properties of the obtained biaxially oriented film are shown in Table 1.
[0161] Comparative Example 8
[0162] The method described in Example 1 is different in that the particle size of component D is 500 nm. The preparation process of component D is as follows:
[0163] Under nitrogen protection, 30 kg of mixed carbon tetra B was introduced into a 200 L reactor containing 20 kg of maleic anhydride, 3 kg of dibenzoyl peroxide and 100 L of isoamyl acetate. The copolymerization pressure was 1.2 MPa, the copolymerization temperature was 100 ° C, and the copolymerization time was 8 h.
[0164] The copolymerization product was passed into a flash separator for gas-liquid separation at 25°C and 0MPa. The obtained liquid-solid mixture was further centrifuged in a centrifugal separator at 4000rpm for 20min for liquid-solid separation to obtain a solid product, which was then washed with hexane. The filter cake obtained by filtration through a sand core funnel was vacuum dried at 90°C for 8h to obtain a copolymer powder. The copolymer powder was tested, and the content of maleic anhydride structural units was 52.8 mol%; the average particle diameter was 500nm; and finally a film with an average thickness of 25μm was obtained, which consisted of an upper surface layer, a core layer and a lower surface layer, and the raw materials of each layer were the polyamide composition of this comparative example. The properties of the obtained biaxially oriented film are shown in Table 1.
[0165] Comparative Example 9
[0166] According to the method described in Example 1, the difference is that the amount of component C added is 60 parts by weight, and the blended polyamide comprises 36 parts by weight of PA6-1, 4 parts by weight of PA612-1, and 60 parts by weight of MXD6;
[0167] The resulting cast film was broken during the biaxial stretching process.
[0168] Table 1
[0169]
[0170] It can be seen from the data in Table 1 that the present invention can obtain a biaxially stretched polyamide film with high light transmittance, low haze and low stretching temperature.
[0171] From the attached Figure 1 and 2 It can also be seen that the structures of the cast films obtained in the examples of the present application and the comparative examples are different. The crystals of the cast film of the example are irregularly striped, and the density of the spherulites with complete structures is low, while the crystals of the cast film of the comparative example are spherulites with complete structures and high spherulite density. The more complete the crystal structure, the stronger the hydrogen bonds between its molecular chains, and a greater stretching force needs to be applied during the stretching process. The cast film of comparative example 1 broke during the stretching process.
[0172] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A low haze polyamide composition comprising component A and / or component B, and component C and component D; in, Component A is PA6; Component B is PA612; Component C is MXD6; component D is mixed olefin-maleic anhydride copolymer microspheres.
2. The low haze polyamide composition according to claim 1, characterized in that: The weight ratio of component A to component B is (0-100):(100-0), preferably (60-95):(5-40); more preferably (70-90):(10-30).
3. The low haze polyamide composition according to claim 1, characterized in that: The weight ratio of component C to component (A+B) is (5-50):(50-95), preferably (10-40):(60-90).
4. The low haze polyamide composition according to claim 1, characterized in that: Taking the total weight of component A, component B and component C as 100 parts by weight; The weight ratio of the component D to the component (A+B+C) is (0.01-0.35):100, preferably (0.03-0.2):100, and more preferably (0.03-0.1):
100.
5. The low haze polyamide composition according to claim 1, characterized in that: The PA6 has a relative viscosity of 1.5-5.0, preferably 2.0-4.0, and the viscosity test standard is ISO307; and / or, The PA612 has a relative viscosity of 1.5-5.0, preferably 2.0-4.0, and the viscosity test standard is ISO307; and / or, The relative viscosity of the MXD6 is 1.5-5.0, preferably 2.0-4.0, and the viscosity test standard is ISO307.
6. The low haze polyamide composition according to claim 1, characterized in that: The component D is a mixed olefin-maleic anhydride copolymer microsphere, preferably with a particle size of 100 to 300 nm; Preferably, the content of maleic anhydride structural units in the mixed olefin-maleic anhydride copolymer microspheres is 40 to 70 mol %, preferably 45 to 60 mol %, and more preferably 48 to 55 mol %.
7. The low haze polyamide composition according to claim 1, characterized in that: The mixed olefin-maleic anhydride copolymer microspheres are copolymer microspheres of maleic anhydride and C4 olefins prepared by copolymerization of mixed C4 and maleic anhydride in the presence of nitrogen, an initiator and an organic solvent; preferably, the copolymerization temperature is 60 to 100° C., preferably 80 to 100° C., and the copolymerization pressure is 0.5 to 2.5 MPa, preferably 0.8 to 2 MPa.
8. The method for preparing a low haze polyamide composition according to any one of claims 1 to 7, characterized in that The following steps are involved: The components including the component A and / or the component B, the component C and the component D are blended to obtain the low haze polyamide composition.
9. A polyamide molded article made from the low haze polyamide composition according to any one of claims 1 to 7, wherein the content of the low haze polyamide composition is 80 to 100% by weight.
10. The film made from the low haze polyamide composition according to any one of claims 1 to 7, preferably a biaxially stretched film; preferably, the biaxially stretched film has a thickness ranging from 5 to 120 microns, preferably from 10 to 100 microns.
11. The method for preparing the thin film according to claim 10, comprising the following steps: The low haze polyamide composition is melt-extruded and cast into a sheet to obtain a polyamide sheet; the polyamide sheet is stretched to form a film; the stretching is preferably biaxial stretching; the stretching temperature is preferably 90 to 185°C, more preferably 95 to 175°C.
12. Use of the low haze polyamide composition according to any one of claims 1 to 7 or the film according to claim 10.
Citation Information
Patent Citations
Biaxially stretched, multi-layereded polyamide film and production method thereof
CN101152764A
Polyvinyl alcohol matte film, polyvinyl alcohol composition and preparation method of polyvinyl alcohol matte film
CN109721908A
Polyamide-polyester alloy composition and a polyamide 6-polybutylene terephthalate alloy
CN111100447A
Application of copolymer as light stabilizer, and composite light stabilizer and preparation method and application thereof
CN111808372A
Mixed olefin grafted microsphere reinforced flame-retardant nylon 6 composition and preparation method thereof
CN112708261A